Gross Anatomical, Histologic and Histometric Studies on the Thyroid Gland of Goat (Capra hircus) in Different Age Groups - Nandeshwar, N.C.; Banubakode, S.B.; Mainde, U.P.; Rupali Charjan,; Ayesha Boddupalli,; Singh, Anand; P.D. Bhole, (Indian Journal of Veterinary Anatomy, 2024)
The present study was conducted on 36 healthy non-descript male and female goats, divided into 3 different groups. The thyroid gland was dark brown colored and observed to be located between the larynx and 4thtracheal rings. Its morphometry was influenced by age, being bigger in adults. The capsule was made up of collagen and a few elastic fibers which were denser in old animals. The parenchyma of the gland showed follicles varying in shape but mostly irregularly spheroid follicles were noticed. The parafollicular cells observed within the follicular epithelium had lighter cytoplasm and oval nuclei.Although no significant sex difference wasnoticed, but micrometrical dimensions were found to be increased with the age.